(untitled) (Global Journal of Management and Business Research, 2018)
This study reports the result from the study of safety and health management and organizational productivity in the aluminum sector of Owerri Imo State A 16 item questionnaire was used to elicit responses from 40 respondents purposefully sampled by those who have the background of the study Both descriptive and inferential statistics T-Test were used to analyze the data from the survey The study established the relationship between safety and health policy and operating cost on the one hand and safety and health training on the other hand The two tested hypotheses were statistically significant at 5 level The study recommends that there is a need in making sure that Safety and Health management is accorded top priority in organizational activities as health is wealth